Penggunaan Media Pembelajaran Berbasis Visual untuk Meningkatkan Perhatian Siswa Pada Mata Pelajaran IPS Siswa Sekolah Dasar - Panut Setiono; Eka Puspita Sari (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2016)
The purpose of this study was to increase the attention of class III students in social studies subjects through visual-based learning media, which directed students to be eager to learn, students seemed serious in learning, and many students did learning activities that not only listened to the teacher's description, but also did a lot other activities. The type of research used is Classroom Action Research (CAR) conducted by researchers and teacher collaborators in class III SDN No.111 / 1 Komplek Air Panas through 3 cycles. Where each cycle is held 2 times. Each cycle consists of four activities, namely planning, action, observation and evaluation, and reflection. Based on the results of the study, the results achieved in each cycle have increased. In the first cycle of observation, the teacher's activity got a score of 63%, observing the attention of students getting a score of 65.52% and learning outcomes gained an average of 58.52. In the second cycle of observation the teacher's activities scored 73%, observations of students' attention gained 75.76% and student learning outcomes gained an average of 68.67. In the third cycle observation of teacher activities scored 89%, observation of students' attention gained a score of 83.88% and student learning outcomes gained an average of 81.61. Based on the results obtained, it can be seen that through visual-based learning media can increase students' attention on social studies subjects in grade III SDN No.111 / 1 Komplek Air Panas .